(untitled) (Jurnal Ecosolum, 2019)
The extend remobilization of nutrient on crops so far is known well. However, as we assumed that the re-translocation of the particular nutrient as nitrogen has a strong affect to the terpenoid metabolic like citronellol. In many cases, the environment stress such as drought induced volatile compound as citronellol leave in citrus. The aim of experiment is to observe the distribution of citronellol as consequence the distribution of nitrogen on different layer of tree canopy. The method of the research obtain the samples of leaves which were collected from different layer of citrus canopy from 10 samples of trees on each part of field: bottom layer, middle layer and upper layer of canopy. The randomized leaves were collected and analyzed by the HPLC and Spectro-photometer to measure the content of nitrogen and glutamate distribution correlated to citronellol content. The results presents that the closely correlation of distribution of nitrogen between bottom layer, middle layer and upper layer of lemon leaves to produce glutamate and citronellol. The remobilization of nitrogen from bottom leaves content 1.35 ppm followed by middle leaves 1.4 ppm and the highest is the upper leaves is 1.65 ppm. As consequence that the glutamate and citronellol were increase as the same trend as those nutrients distribution. The glutamate seems to be the precursor of the secondary metabolic which was converted into the harvested leaves of citrus. Increasing of 5% glutamate from the upper leaves to the middle leave and the bottom leaves seem to be much accumulated of citronellol content in the bottom leaves.